PENGARUHI PELAYANAN PAJAK DAN SANKSI PAJAK TERHADAP KEPATUHAN MEMBAYAR PAJAK PENGHASILAN PADA KARYAWAN PT. KENCANA INTI PERKASA - Putri Wahyuni (JRMB (Jurnal Riset Manajemen & Bisnis), 2018)
This study aims to investigate the effect of tax service and sanctions on compliance to pay income tax. It is conducted at PT. Kencana Inti Perkasa and employing the population and sample from the employees of this enterprise. The sample of the study is 87 respondents by using purposive sampling and the data is gained from respondenses through questionnaire which has been spread up around the population and analyzed by statistical approach includes a test of validity, reliability test, test the assumptions of regression analysis, classical hypotesis, multiple regression analysis, testing the hypothesis through a test of determination, t-test and f- test. Both tax services (X1) and tax sanction (X2) stand as independent variables while the employees’ complience to pay income tax is as dependent variable (Y). The results shows that regression analysis Y = 8,747 + 0,442 X1 + 0,650 X2 + 0,05. Partially indicate that taxes servise (X1) effects to compliance pays income tax of employees (Y) with a value of the tcount  of 8,781 1,66298. The most influential tax sanctions (X2) compliens significantly to pay income tax with a value of the tcount of 5,633 1,66298. Simultaneously the tax services and tax sanctions give effect significantly to compliance pays income tax of employess of PT. Kencana Inti Perkasa with a value of fcount  of 95,989 3,11. Determination of coefficient of 96,9% indicates that the variable pay income tax compliance can be explained by the variables of the tax services and tax sanctions, while the rest of 30,4% explained by other variables.